Antibiotics potentiating potential of catharanthine against superbug Pseudomonas aeruginosa. Issue 16 (10th December 2018) - Dwivedi, Gaurav Raj; Tyagi, Rekha; Sanchita,; Tripathi, Shubhandra; Pati, Sanghamitra; Srivastava, Santosh K.; Darokar, Mahendra P.; Sharma, Ashok
Abstract : Multidrug resistance (MDR) put an alarming situation like preantibiotic era which compels us to invigorate the basic science of anti-infective chemotherapy. Hence, the drug resistant genes/proteins were explored as promising drug targets. Keeping this thing in mind, proteome of Pseudomonas aeruginosa PA01 was explored, which resulted in the identification of tripartite protein complexes (MexA, MexB, and OprM) as promising drug target for the screening of natural and synthetic inhibitors. The purpose of present investigation was to explore the drug resistance reversal potential mechanism of catharanthine isolated from the leaves of Catharanthus roseous . Hence, the test compound catharanthine was in silico screened using docking studies against the above receptors, which showed signiﬁcant binding affinity with these receptors. In order to validate the in silico findings, in vitro evaluation of the test compound was also carried out. In combination, catharanthine reduced the minimum inhibitory concentration MIC of tetracycline (TET) and streptomycin up to 16 and 8 folds, respectively. Further, in time kill assay, catharanthine in combination with TET reduced the cell viability in concentration dependent manner and was also able to reduce the mutation prevention concentration of TET. It was also deduced that drug resistance reversal potential of catharanthine was due to inhibition of the efflux pumps. Abstract :